Factors Affecting People’s Decision to Adopt OVO - Richard Irawan (iBuss Management, 2019)
Technology has been developing over the years and mobile payment system has become common these days. However, research on mobile payment is still scarce and there is a need for research, especially the intention to adopt mobile payment system. OVO is a mobile payment system that was developed recently and has gathered quite lot of users. This research is aimed to study the factors affecting behavior intention which are performance expectancy, effort expectancy, social influence, facilitating condition, perceived technology security, and personal innovativeness.This research is done by distributing questionnaires to people in Indonesia who have never use OVO, but have the understanding of what OVO is, with sample sizes of 98 and are randomly chosen. The researcher analyzes the data using Multiple Linear Regression Analysis, which result indicates that independent variables used in this research have simultaneous impact toward behavior intention. Individually, only personal innovativeness, perceived technology security, and performance expectancy have significant influence toward adoption intention. In addition, personal innovativeness has the highest significant level towards behavior intention. Keywords: Adoption Intention, Behavioral Intention, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition, Perceived Technology Security, Personal Innovativeness.